2019
DOI: 10.1002/pen.25093
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behavior of thermoplastic composites reinforced with fibers enzymatically extracted from Ampelodesmos mauritanicus

Abstract: This work investigates the morphology, the thermal, and mechanical properties of technical fibers extracted from the Ampelodesmos mauritanicus (Diss) grass using a process that combines mechanical, mild chemical, and enzymatic steps. The structure and the thermal stability of Diss fibers make them suitable as a reinforcing filler in polymer composites, which was assessed by manufacturing biocomposites with improved stiffness and a tensile strength not degraded by Diss fibers when compared to those of a commodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In addition, the extraction method clearly influences the mechanical properties of the fibers. Bourahli (2014) found an average tensile stresses of 149 ± 81, while Sarasini et al (2019) found a low one of 19 MPa.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, the extraction method clearly influences the mechanical properties of the fibers. Bourahli (2014) found an average tensile stresses of 149 ± 81, while Sarasini et al (2019) found a low one of 19 MPa.…”
Section: Introductionmentioning
confidence: 98%
“…Lately, Achour, Ghomari, and Belayachi (2017) investigated the effect of various treatments and the fibers loading rate on the physical, mechanical and thermal properties of the composite Diss fibers/ cement. Very recently, Sarasini et al (2019) studied the reinforcement of PP and PLA matrix by Diss fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This perennial plant belongs to the family Poaceae rich in fibers (Damerdji 2012). Recently, this plant attracted the attention of researchers and particularly to be used as a reinforcement for cement composites (Merzoud and Habita 2008) (Achour, Ghomari, and Belayachi 2017), and polymer composites (Bourahli 2014) (Sarasini et al 2019). In terms of extraction methods, chemical composition, treatments, mechanical and thermal behavior, Diss fibers have been subject to several studies in the literature (Merzoud and Habita 2008) (Bourahli and Osmani 2013) (Achour, Ghomari, and Belayachi 2017) (Sarasini et al 2019) (Nouri et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional synthetic fibers (glass, carbon, aramid, etc. ), natural fibers, especially plant fibers, show many appealing characteristics as low cost, low density, abundantly available, renewability, high strength, and elasticity modulus, thus demonstrating great potential in the new generation of sustainable composites . Many researchers attempted to prepare more economical and environmentally friendly polymer composites by adding various natural fibers into the polymer matrices.…”
Section: Introductionmentioning
confidence: 99%